Co‐occurrence of Aicardi–Goutières syndrome type 6 and dyschromatosis symmetrica hereditaria due to compound heterozygous pathogenic variants in ADAR1: a case series from India. (4th January 2021) - Sathishkumar, D.; Muthusamy, K.; Gupta, A.; Malhotra, M.; Thomas, M.; Koshy, B.; Jasper, A.; Danda, S.; George, R.
Abstract: Aicardi–Goutières syndrome type 6 (AGS6) and dyschromatosis symmetrica hereditaria (DSH) are allelic disorders caused respectively by biallelic and heterozygous pathogenic variants in ADAR1 . We report three unrelated children presenting with features of both AGS6 and DSH, two of whom had compound heterozygous pathogenic variants in ADAR1 . We also describe the novel genetic variants in our cases and review the literature on association of ADAR1 ‐related AGS6 and DSH with these phenotypes.